Towards Sustainable Water Use: Factors Influencing Farmers’ Participation in the Informal Groundwater Markets in Pakistan - Razzaq, Amar; Xiao, Meizhen; Zhou, Yewang; Anwar, Mumtaz; Liu, Hancheng; Luo, Fang (Frontiers in Environmental Science, 2022)
Informal groundwater markets have spontaneously developed in Pakistan due to the heterogeneity of farmers' resource endowments, irrigation water shortages, and productivity gains of groundwater. Evidence shows that water allocation through formal or informal water markets can result in significant benefits for buyers and sellers and improve sustainable water use. Existing literature on water markets generally takes only buyers' perspectives into account when studying the factors influencing the purchase of groundwater for irrigation. In contrast, we look at the perspectives of both buyers and sellers to investigate farmers' participation in informal water markets. We conducted this study in the three agroecological zones of Punjab. The data was collected from a sample size of 360 farmers, with an equal proportion of water buyers, sellers, and self-users. Cragg's double hurdle model was used to investigate the factors influencing the extent of water buying or selling. Results of the demand side analysis show that educated has negative correlation with water market participation and level of water purchasing. In addition, large farmers are less likely to buy water, indicating that the majority of farmers in water markets are smallholders. However, the degree of land fragmentation, soil fertility, and adoption of improved seeds each have may increase water market participation. Water cost and farmers’ family size has negative impact on level of water purchasing. The results of supply side analysis show that tubewell capacity, degree of land fragmentation, and the number of operational tubewells at a given farm have a positive relationship with the likelihood of selling water. When it comes to the amount of water sold, two factors that positively influence the extent of water selling are the income from water sales and the degree of land fragmentation. Finally, we discuss the implications of these results for sustainable water extraction in the water markets.